2021
DOI: 10.1021/acs.analchem.1c04022
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR/Cas12a-Mediated Dual-Mode Electrochemical Biosensor for Polymerase Chain Reaction-Free Detection of Genetically Modified Soybean

Abstract: A clustered regularly interspaced short palindromic repeats (CRISPR)/ Cas12a-mediated dual-mode electrochemical biosensor without polymerase chain reaction (PCR) amplification was designed for sensitive and reliable detection of genetically modified soybean SHZD32-1. A functionalized composite bionanomaterial Fe 3 O 4 @AuNPs/DNA-Fc&Ru was synthesized as the signal unit, while a characteristic gene fragment of SHZD32-1 was chosen as the target DNA (tDNA). When Cas12a, crRNA, and tDNA were present simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Deng et al [61] used a label-free sensing technology to directly reflect the differences in DNA hybridization with changes in electrode performance. Ge et al [62] recently reported a CRISPR/Cas12a-mediated dual-mode PCR, genosensor, and sequence became burst keywords over the next few years, but they did not last very long. In 2018, amplification and reduced graphene oxide became the new burst keywords until 2021.…”
Section: Keyword Analysis and Evolution Of The Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…Deng et al [61] used a label-free sensing technology to directly reflect the differences in DNA hybridization with changes in electrode performance. Ge et al [62] recently reported a CRISPR/Cas12a-mediated dual-mode PCR, genosensor, and sequence became burst keywords over the next few years, but they did not last very long. In 2018, amplification and reduced graphene oxide became the new burst keywords until 2021.…”
Section: Keyword Analysis and Evolution Of The Fieldmentioning
confidence: 99%
“…Deng et al [61] used a label-free sensing technology to directly reflect the differences in DNA hybridization with changes in electrode performance. Ge et al [62] recently reported a CRISPR/Cas12a-mediated dual-mode did not last very long. In 2018, amplification and reduced graphene oxide became the new burst keywords until 2021.…”
Section: Keyword Analysis and Evolution Of The Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…This is advantageous when compared to the above-mentioned ratiometric strategies that also showed two readouts, however, the two readouts are from the same detecting method. For example, electrochemical/ECL dual- mode, 138,139 electrochemical/photoelectrochemical (PET) dualmode, 140,141 and ECL/PET dual-mode 142 sensing strategies have been reported for improved cross-validating detection. Zhou et al combined the electrochemistry method and surface-enhanced Raman scattering (SERS) technology to realize a dual-mode assay for miRNA.…”
Section: Ratiometric or Dual-modal Ecl Biosensingmentioning
confidence: 99%